Mudanças espaço-temporais na estrutura e composição da comunidade zoobentônica em lagos do médio Rio Doce, Minas Gerais, Brasil, colonizados por Melanoides tuberculatus (Gastropoda, Thiaridae) - Natalia Murta de Lima Dornelas (2013)
One of the main causes of biodiversity and environmental quality loss in the world is the introduction of exotic species and studies to detect and quantify this impact are important, although still scarce. One of the threats to aquatic biodiversity in the region of the Middle Rio Doce Valley is the invasive species of gastropod Melanoides tuberculatus. This study aims to analyze population structure and the invasion stage of M. tuberculatus from 2004 to 2009 and assess changes associated with the presence ofM.tuberculatus on the structure and composition of the benthic macroinvertebrate community. Biological, physical and chemical data were collected during periods of drought and rainfall from 2004 to 2009. The sediment was sampled for benthic community analyses with a manual net (mesh 350mm). The results show that the structure of populations of M. tuberculatus shows similar age distribution among lakes, showing large number of young (classes 1 and 2), followed by a drastic reduction in the abundance of individuals from the class 3. On lake Dom Helvécio mortality in class 3 is higher than in other classes, although lake Jacaré mortality was higher in class 2 (66%). Considering the whole study period, lake had the highest density of M. tuberculatuswith c. 100,000 ind./m2 followed by Dom Helvécio with 68,640 ind./m2, and finally Águas Claras with 37,752 ind./m2. The mollusk was found in all sampled points indicating that the distribution is generalized to all lakes, besides being present in high density in most campaigns. Thus, the level of invasion proposed by Collauti e MacIsaac (2004) is V (dominant and widespread distribution) for all lakes, stage difficult toreverse. The lakes within the Rio Doce State Park have greater species richness and greater diversity of benthic invertebrate than those located in its surroundings. These results also show that low equitability values coincide with peaks in the abundance of M. tuberculatus, although equitability shows no significant difference between the lakes. Despite the large size and dendritic shape of lake Dom Helvécio, the same amount of taxa recorded in it was also recorded in lake Gambazinho which has the lowest margin development, indicating the influence of invasive species in the crash of the diversity of the environment. Among the scrapers species, Littoridina aff. miaulis correlates positively with M. tuberculatus and its population has declined possibly as a result ofhigh densities of this invasive species in Dom Helvécio. Also in this lake, the increased abundance of Physa sp. might be a case of apparent competition through facilitation. Average limnological characteristics of the lakes are quite similar, except conductivity and silicate that were lower in Gambazinho lake.